TNFα and IL‐17A are differentially expressed in psoriasis‐like vs eczema‐like drug reactions to TNFα antagonists. (22nd November 2017) - Deubelbeiss, Cornelia; Kolios, Antonios G. A.; Anzengruber, Florian; French, Lars E.; Yawalkar, Nikhil; Kempf, Werner; Kerl, Katrin; Meier, Barbara; Navarini, Alexander A.
Abstract : Background: Tumor necrosis factor α (TNFα) blocking drugs are in use for a wide range of autoimmune disorders. In up to 5% of patients, this class of drugs produces puzzling cutaneous side effects that are the subject of this investigation, namely psoriasiform and eczema‐like skin inflammation. These side effects can occur after any time of treatment and regardless of the underlying disorders. The exact pathophysiology is as yet unknown. Methods: A total of 33 patients (19 female, average age 52 years) who had a cutaneous reaction to infliximab, adalimumab or etanercept were included. The type of inflammatory reaction was determined, and the corresponding cytokine expression was evaluated by immunohistochemistry for TNFα, IL‐1β, IL‐22, IL‐6, IL‐17A, IL33, IL‐8 and IL‐36α (semi‐quantitative grading system from − to ++++). In addition, RNA expression levels of IL‐17A and TNFα were confirmed by quantitative real‐time PCR. Results: IL‐17A ( P  < .039) and TNFα ( P  < .008) were expressed at significantly higher levels in psoriasis or pustular‐like reactions (PPR) compared to eczematous‐like reactions (ELR). There was no significant difference in the expression of IL‐1β, IL‐22, IL‐6, IL‐33, IL‐8 and IL‐36α between PPR and ELR. Conclusion: TNFα and IL‐17A are both cytokines known to be involved in psoriasis but less so in non‐psoriasiform dermatitis or eczema. Therefore, their overexpression in PPR is plausible and suggests that the pathogenesis of PPR mirrors at least in part those of psoriasis. Further investigations will define the exact role of these cytokines in rare cutaneous side effects of anti‐TNFα therapy. Our results suggest that IL‐17A inhibition could be a therapeutic option in patients with anti‐TNF induced psoriasis.